Short-course eflornithine in Gambian trypanosomiasis: a multicentre randomized controlled trial - Jacques Pépin; Nzambi Khonde; Faustine Maiso; Félix Doua; Shabbar Jaffar; Stéphane Ngampo; Bokelo Mpia; Dawson Mbulamberi; Felix Kuzoe (The World Health Organization, 2000)
OBJECTIVE: A randomized controlled trial was conducted to determine whether 7 days of intravenous eflornithine (100 mg/kg every 6 h) was as effective as the standard 14-day regimen in the treatment of late-stage Trypanosoma brucei gambiense trypanosomiasis. METHODS: A total of 321 patients (274 new cases, 47 relapsing cases) were randomized at four participating centres in Congo, Côte d'Ivoire, the Democratic Republic of the Congo, and Uganda to one of these treatment regimens and followed up for 2 years. RESULTS: Six patients died during treatment, one of whom was on the 7-day regimen, whereas the other five had been on the 14-day regimen (P = 0.2). The response to eflornithine differed markedly between Uganda and other countries. Among new cases in Uganda, the 2-year probability of cure was 73% on the 14-day course compared with 62% on the 7-day regimen (hazard ratio (HR) for treatment failure, 7-day versus 14-day regimen: 1.45, 95% CI: 0.7, 3.1, P = 0.3). Among new cases in Côte d'Ivoire, Congo, and the Democratic Republic of the Congo combined, the 2-year probability of cure was 97% on the 14-day course compared with 86.5% on the 7-day regimen (HR for treatment failure, 7-day vs 14-day: 6.72, 95% confidence interval (CI): 1.5, 31.0, P = 0.003). Among relapsing cases in all four countries, the 2-year probability of cure was 94% with 7 days and 100% with 14 days of treatment. Factors associated with a higher risk of treatment failure were: a positive lymph node aspirate (HR 4.1; 95% CI: 1.8-9.4), a cerebrospinal fluid (CSF) white cell count >100/mm³ (HR 3.5; 95% CI 1.1- 10.9), being treated in Uganda (HR 2.9; 95% CI: 1.4-5.9), and CSF trypanosomes (HR 1.9; 95% CI : 0.9-4.1). Being stuporous on admission was associated with a lower risk of treatment failure (HR 0.18; 95% CI: 0.02-1.4) as was increasing age (HR 0.977; 95% CI: 0.95-1.0, for each additional year of age). DISCUSSION: The 7-day course of eflornithine is an effective treatment of relapsing cases of Gambian trypanosomiasis. For new cases, a 7-day course is inferior to the standard 14-day regimen and cannot be recommended.